“Cruel Capes”: a novel; and the nexus between fact and imagination: a discourse of the historical fiction genre in contemporary novels: an exegesis - Van Zeller, Marcia (Curtin University, 2014)
The allegedly daring deeds of 16-year-old Grace Bussell and Sam Isaacs – legendary heroes of the 1876 Georgette shipwreck – are questioned in the historical novel, Cruel Capes, the creative component of this thesis. The production of the accompanying exegesis has informed the creative and ethical approach to revisioning the Georgette rescue. Both components strive to answer the central research question: How can a writer of historical fiction ethically negotiate the divide between fact and imagination?